The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4049/jimmunol.1500871
|View full text |Cite
|
Sign up to set email alerts
|

IL-3 Maintains Activation of the p90S6K/RPS6 Pathway and Increases Translation in Human Eosinophils

Abstract: IL-5 is a major therapeutic target to reduce eosinophilia. However, all of the eosinophil-activating cytokines IL-5, IL-3, and GM-CSF are typically present in atopic diseases including allergic asthma. Due to the functional redundancy of these 3 cytokines on eosinophils and the loss of IL-5 receptor on airway eosinophils, it is important to take IL-3 and GM-CSF into account to efficiently reduce tissue eosinophil functions. Moreover, these 3 cytokines signal through a common β-chain receptor, and yet different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(86 citation statements)
references
References 61 publications
9
77
0
Order By: Relevance
“…DAVID cluster analysis indicates that the hyper-phosphorylated proteins are mostly implicated in intracellular signaling, cytoskeleton organization, RNA binding, regulation of protein translation, and intracellular movement (Table 4 and Supplemental Tables 5, 6, 7 and 8). The present phospho-proteome confirms our previous published study, in which we demonstrated continuous phosphorylation of RPS6KA1 (RSK1), RPS6, and EIF4B by a 14 h activation of EOS with IL-3 (7) . Additionally, we previously found that IL-3-prolonged RPS6KA1 phosphorylation was critical for SEMA7A and FCGR2B translation and protein accumulation (7, 8) , and as described above, SEMA7A and FCGR2B were both highly up-regulated by IL-3.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…DAVID cluster analysis indicates that the hyper-phosphorylated proteins are mostly implicated in intracellular signaling, cytoskeleton organization, RNA binding, regulation of protein translation, and intracellular movement (Table 4 and Supplemental Tables 5, 6, 7 and 8). The present phospho-proteome confirms our previous published study, in which we demonstrated continuous phosphorylation of RPS6KA1 (RSK1), RPS6, and EIF4B by a 14 h activation of EOS with IL-3 (7) . Additionally, we previously found that IL-3-prolonged RPS6KA1 phosphorylation was critical for SEMA7A and FCGR2B translation and protein accumulation (7, 8) , and as described above, SEMA7A and FCGR2B were both highly up-regulated by IL-3.…”
Section: Resultssupporting
confidence: 93%
“…IL-3-enhanced IL3RA is in agreement with the previous finding showing that the surface receptor for IL-3 is enhanced on EOS by a prolonged (~20 h) activation with the ß-chain cytokines (IL-5, GM-CSF, or IL-3) while the amount of surface receptors for IL-5 and GM-CSF are decreased or unchanged, respectively, in the same conditions (22, 23) . The enhanced amount of both IL3RA and CSF2RB explains the unique ability for IL-3 compared to IL-5 and GM-CSF to sustain intracellular signaling in EOS (7, 24) .…”
Section: Resultsmentioning
confidence: 99%
“…To understand the regulation of TNF-α production in primed monocytes, we compared intracellular TNF-α protein levels, TNF mRNA, and primary transcript levels upon LPS stimulation for 1 and 4 h. Although in several experimental models priming of monocyte and macrophages results in chromatin remodeling (20, 2224, 2630), our data support a posttranscriptional regulation of TNF-α production in primed monocytes. Posttranscriptional mechanisms, including modulation of mRNA stability and translation (3335), are increasingly recognized as critical regulators of gene and protein expression also in immune cells (25, 34, 36, 37, 54, 55). Our results demonstrate that inhibition of SIRT2 during priming and of p38 or ERK1/2 (the latter only for GM-CSF primed cells) during LPS stimulation reduces intracellular TNF-α protein levels without significantly modulating TNF RNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-3 is elevated in serum in poorly controlled asthmatic patients, and airway IL-3-positive cells are increased with asthma severity [25, 26]. Furthermore, segmental allergen challenge in mild asthma leads to elevated levels of IL-3 in the BAL fluid [20, 27], and while airway eosinophils display reduced surface α chain for the IL-5 receptor, they show increased IL-3 receptor compared to blood eosinophils [12, 28]. …”
Section: Introductionmentioning
confidence: 99%